Influence of voluntary isocapnic hyperpnoea on recovery after high-intensity exercise in elite short-track speedskaters - randomized controlled trial - Kowalski, T.; Wilk, A.; Rebis, K.; Lohse, K.-M.; Sadowska, D.; Klusiewicz, A. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Respiratory muscle training plays a significant role in reducing blood lactate concentration (bLa) and attenuating negative physiological stress reactions. Therefore, we investigated if voluntary isocapnic hyperpnoea (VIH) performed after a maximum anaerobic effort influences bLa and perceived fatigue level in well-trained speedskaters. 39 elite short-track speedskaters participated in a trial with two parallel groups: experimental and control. All the participants performed the Wingate Anaerobic Test (WAnT). The experimental group performed a VIH-based recovery protocol 20 min after exercise, the control group used passive recovery only. Blood samples were taken 3 and 30 min after the WAnT to measure bLa. Fatigue was self-appraised on a 0-10 perceived rating-of-fatigue (ROF) scale 3 and 30 min after the WAnT. Noteworthy, but not statistically significant changes between the experimental and control groups were observed for changes in bLa (p = 0.101). However, statistically significant changes between the groups were found for ROF (p = 0.003, ?p2 = 0.211, ?2 = 0.106). Moreover, statistically significant interactions between post-exercise bLa clearance and VO2max (p = 0.028) and inspiratory muscle strength (p = 0.040) were observed. Our findings provided preliminary insight that VIH may be an efficient recovery protocol after anaerobic exercise performed by elite athletes. The association between VO2max and post-exercise bLa clearance indicates the vital role of aerobic fitness in repeated-efforts ability in short-track speedskaters. The study was registered at ClinicalTrials.gov as NCT05994092 on 15th August 2023.